Adapting Sichuan Opera facial painting in souvenirs to promote Sichuan Opera - Wu, Yating (2024)
This research examines the use of visual element derived from Sichuan Opera facial cosmetics into the design of tourist souvenirs. The objective is to enhance the promotion of Sichuan Opera culture and foster cultural awareness. Sichuan Opera is a renowned kind of Chinese opera that holds significant historical, cultural, and artistic significance. Although it holds significant value, the task of conserving and advancing this artistic expression is fraught with ongoing difficulties. This study aims to solve these challenges by integrating the Theory of Cultural Symbols and Tourist Souvenir Design Theory to develop a robust theoretical framework. A Mixed research approach was employed, combining qualitative and quantitative methodologies. Primary data was obtained through interviews and questionnaires, while secondary data was collected from academic papers and pertinent literature. The study focused on Chengdu, which is renowned as a cultural hub for Sichuan Opera. The qualitative data were analyzed with the NVivo software, while the quantitative data were handled using the SPSS software. The results suggest that customers recognize and comprehend the symbolic significance of colors in Sichuan Opera facial cosmetics, even though there are few patterns and compositions linked with them. When making purchasing decisions, elements such as cultural significance, distinctiveness, and price play a crucial role. Furthermore, the study encompasses the creation and evaluation of prototype mementos that embody customer preferences, emphasizing the importance of harmonizing cultural authenticity with contemporary design aspects. This study emphasizes the capacity of carefully crafted souvenirs to both safeguard cultural heritage and enhance commercial prosperity. This framework offers a valuable structure for designing tourist souvenirs that are culturally meaningful. It also gives practical guidance for designers and sets a path for future research endeavors.